ANALISA HIDROKUINON DALAM KRIM DOKTER SECARA SPEKTROFOTOMETRI UV-VIS - Azmalina Adriani; Rifa Safira (Lantanida Journal, 2018)
Cosmetics is products used to enhance the appearance of face. Various kinds of cosmetic products are increasingly emerging at this time. One kind of cosmetic is whitening cream. The whitening cream contains of an active substance used to tint black spots on the skin. The active substance which often used in cosmetics is hydroquinone. Hydroquinone is a class of hard drugs whose use must be based on a doctor's prescription. The use of hydroquinone is prohibited on cosmetic preparations that are sold freely, but may be used if under the supervision of a physician 2% (BPOM, 2007). The aim of this study was to determine the existence and level of hydroquinone in whitening cream. The results of the analysis showed that samples A, B, C, D, E, F, H and I were positive for hydroquinone with percentage of hydroquinone was about 0.000168%, 0.000319%, 0.000309%, 0.001188%, 0.00392%, 0.000058%, 0.000521%, 0.000899%, whereas the G sample was not detected.